Antibiotics and Innate Immunity: A Cooperative Effort Toward the Successful Treatment of Infections. (20th July 2020) - Berti, Andrew; Rose, Warren; Nizet, Victor; Sakoulas, George
Abstract: Despite the common ancestry of antimicrobial and immunological science, a divergence driven by artificially construed paradigms in microbiology has placed limits on how we understand the mechanisms of antibiotics in vivo. We summarize recent updates on data that shed light on how antibiotics interact with components of innate immunity.